Characterizing various aspects of the male genital tract barrier function and immunity - Rametse, Cosnet (Department of Clinical Laboratory Sciences, 2025)
There has been significant progress in the management of Human Immunodeficiency Virus-1 (HIV-1) infection and prevention globally since the availability of antiretroviral drugs (ARVs). Due to a combination of ARV availability, increased HIV testing, and the introduction of a range of HIV prevention tools, HIV mortality in Africa has declined. However, HIV remains a global burden that still needs urgent attention, as there is still a high rate of new HIV infections globally and in South Africa. Effective control of this epidemic requires a complete understanding of the mechanisms of transmission and acquisition of this virus. HIV acquisition in men through penile exposure is one of the least studied modes of HIV transmission. Voluntary medical male circumcision (VMMC) is associated with a 60% reduced risk of HIV acquisition through heterosexual intercourse. However, uncircumcised men comprise approximately 70% of the male population worldwide, implying that although an effective prevention method has been shown, many men remain uncircumcised. Furthermore, it is not well understood why there remains a group of circumcised males who remain susceptible to infection. Understanding the immune milieu in the male genital tract may reveal additional HIV susceptibility mechanisms and factors that can be used as a foundation for alternative HIV preventative strategies. This PhD thesis examines barrier function, the density of HIV target cells and various expressed epithelial barrier proteins and genes in different anatomical sites of the intact penis before VMMC and in foreskin tissue after surgical removal. How these measurements are impacted by asymptomatic STIs is explored. The central hypothesis is that the inner foreskin has a relatively reduced barrier function compared to the other penile sites, which is further reduced by the presence of asymptomatic STIs (aSTIs). To test this hypothesis, the following aims were explored: 1. To describe the prevalence of aSTIs, including Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and Mycoplasma genitalium at two medical circumcision clinics in the Western Cape, South Africa. 2. To characterize in vivo and ex vivo penile barrier function, represented by transepithelial water loss (TEWL), surface hydration and water content in the glans, foreskin and shaft and further examine how this is impacted by common aSTI and VMMC. 3. To evaluate inflammatory inner and outer foreskin changes associated with aSTIs. 4. To compare spatial transcriptomic patterns in macrophages and epithelial cells between the inner and outer foreskin in the presence of an aSTI. 5. To examine the impact of in vivo Oral Pre-Exposure Prophylaxis (PrEP) on claudin-1 expression and lymphoid/myeloid cells in the foreskin (Published manuscript chapter) Methods Male volunteers who were undergoing VMMC were recruited from community clinics in Retreat, TC-Newman and Mitchells Plain, Western Cape. Multiplex PCR testing was performed on first-pass urine samples collected from 320 HIV-negative male participants to screen for the prevalence of common curable aSTIs: Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and Mycoplasma genitalium. Penile in vivo hydration (n=203) was measured using vapometers, moisture meters SC and D, epi-D to measure proxy barrier function in the absence and presence of an aSTI. Longitudinal measurements were made at 2, 12 (n=28) and 24 weeks (n=16) after VMMC. Foreskin (FS) tissue was collected from a subset of 96 males and examined using histological scoring and gene expression using RTqPCR of Filaggrin, Involucrin, E-cadherin and Claudin. Spatially resolved gene expression in CD68+ macrophages and pan-cytokeratin epithelial cells was made from 8 foreskin tissue samples dissected into inner and outer tissue. Using a DeltaVision Elite microscope, the density of CD4+CCR5+, CD1a+ cells, and percent claudin-1 expression were analyzed in 144 male participant foreskin tissue samples from a randomized on-demand pre-exposure prophylactic clinical trial. Results The overall prevalence of asymptomatic STIs was 15.9%, where the highest prevalence was Chlamydia (12.2%) followed by Mycoplasma genitalium (4.38%,). Marital and educational status were significantly associated with a lower risk of any STI. In vivo measurements of the penile glans, inner foreskin and shaft barrier function show that the trans-epithelial water loss (TEWL) of the inner foreskin (median 27.6 g/hr/m2 ) and glans (median 22.3 g/hr/m2 ) of uncircumcised males was significantly higher compared to the shaft (median 16.2 g/hr/m2 ) of the penis (p<0.0001). Analysis by aSTI status revealed that in the presence of an aSTI, stratum corneum surface hydration in the penile glans was significantly higher (97.4au vs 52.3au; p=0.038). Six months post-circumcision, TEWL in the glans was significantly decreased (p=0.011) from baseline (pre-VMMC), matching that of the shaft. Histological measurements show that total immune cell density was higher in aSTI+ (n=38) vs aSTI- males (n=58), in the epidermis (24.6 vs 10.4 cells /m2 p=0.002), papillary dermis (119.9 vs 61.4 cells/m2 , p=0.014) and reticular dermis (13.6 vs 6.5 cells/m2 , p=0.03). These were predominantly lymphocytic infiltrates that were largely in the papillary dermis. Claudin-1 percent expression was significantly decreased in the inner foreskin compared to the outer foreskin in the presence of an aSTI. This was matched by increased penile glans surface hydration in the presence of an aSTI (58.3 vs 105.6 au, p=0.003). Transcriptomic data showed that in the presence of asymptomatic chlamydia infection, macrophages, and epithelial cells of the inner foreskin showed predominant upregulation of immune-associated genes and pathways such as increased HLA-DQA1, HLA-DQB1 and HLA-DRB1, IL7R expression. Whereas the outer foreskin showed significant downregulation in protein synthesis genes. Examining the impact of ARV alone on the on foreskin immune and barrier function markers in a randomized PrEP study, showed no significant difference in the density of CD4+CCR5+ or CD1a+ cells in foreskins between treatment arms compared with the control arm. Claudin-1 expression was 34% higher (p=0.003) relative to controls in the ARV arm, but after multiple comparisons was no longer statistically significant. Conclusions The difference in TEWL between those with and without an aSTI showed that the uncircumcised penis has a lower barrier function compared to the penis after VMMC. Additionally, the presence of an aSTI significantly increased inflammatory cells in the foreskin epidermis and dermis, with most infiltrates localizing within the papillary dermis. This is associated with decreased expression of Claudin in the inner foreskin (hence reduced barrier integrity) and increased moisture in the glans. These findings show that aSTI's alter gene expression in key immunological cells and in epithelia that have implications for potentially elevating the risk of HIV infection in uncircumcised males. This PhD is also the first to show that oral dosage and timing of on-demand PrEP have no effect on the numbers or anatomical location of lymphoid or myeloid HIV target cells in foreskin tissue. Overall, The high burden of chlamydia and concurrent STIs highlights the urgent need to improve the prevention, detection, and appropriate management of sexually-acquired infections in young men as they profoundly impact epithelial integrity and immunological events in the foreskin. Screening of aSTIs should be encouraged among young men.